Stres Dapat Mengganggu Proses Spermatogenesis pada Mencit - Yuni Sufyanti Arief (Jurnal Ners, 2011)
Introduction: This study aimed to determine the effect of stress on the process of spermatogenesis and testosterone levels of mice (Mus musculus) male.Method: This was an experimental study using a completely randomized design. The variables examined were the number of spermatogenic cells (spermatogonia, spermatocytes, and spermatids oval) and testoseron levels. Data analysis using oneway analysis of variance (ANOVA), test a small real difference (LSD) 5%, and the kruskal wallis test. This study used 36 mice (Mus musculus) male age 2 months with 20–40 gram body weight divided into 4 groups. The control group (subcutaneous injection of 0.1 ml physiological saline), subcutaneous epinephrine injection group 0.001 mg/20 g BW, subcutaneous epinephrine injection group 0.005 mg/20 g BW, the subcutaneous injection of epinephrine 0.01 mg/20 BB gr.Result: The results show that the analysis of spermatogenic cells (spermatogonia, spermatocytes, and spermatids oval), that repeated exposure to epinephrine with different doses showed that there was a significant decrease. The average decline in a row in the treated group (P1, P2, P3) compared with the control group (K0) for spermatogonia was 28.8%, 42.4%, 45.5%, to spermatocytes was 13.7%, 37.4%, 38.9% and for oval spermatids was 33.3%, 44.2%, 50.4% Having followed by LSD 5% found that there were significant differences for almost all groups except the pair P2–P3 groups for the number of spermatogonia, spermatocytes, and partner groups P1–P2 and P2–P3. As for the blood serum levels of testosterone hormone mice showed no significant decrease.Discussion: Administration of high doses of epinephrine (as stressor) can lead to bottlenecks in the process of spermatogenesis as indicated by decreased number of spermatogenic cells but not cause a decrease in testosterone levels.